ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA DALAM MENYELESAIKAN SOAL ARITMETIKA SOSIAL DALAM PEMBELAJARAN BERBASIS LESSON STUDY FOR LEARNING COMMUNITY DITINJAU DARI KECERDASAN LOGIS MATEMATIS - Yunita, Nindya Wulan; Hobri, H; Oktavianingtyas, Ervin; Sunardi, S; Yudianto, Erfan (Kadikma, 2018)
This research describes about the critical thinking ability of SMP Negeri 4 Jember students in solving social arithmetic problem. Data collection methods which were used are tests, observations, and interviews. The research subjects consist of 3 students where one student in the category of high mathematical logic intelligence, one student in the category of medium mathematical logic intelligence, and one student in the category of low mathematical logic intelligence. In LSLC-based learning, students in the category of high mathematical logic intelligence included in TKBK 4 were very critical, students in the category of medium mathematical logic intelligence included in TKBK 2 were quite critical, and students in the category of low mathematical logic intelligence included in TKBK 0 were not critical. In the critical thinking ability test, students in the category of high mathematical logic intelligence included in TKBK 4 were very critical, students in the category of medium mathematical logic intelligence were included in TKBK 3 were critical, and students in the category of low mathematical logic intelligence included in TKBK 2 were quite critical. The higher the category of mathematical logic intelligence by the subject then the higher student’s critical thinking ability. Keywords: critical thinking ability, mathematical logic intelligence, lesson study for learning community